Faktor-Faktor Yang Mempengaruhi Kehamilan Yang Tidak Diinginkan Pada Remaja - Wulandari, Safitri (Jurnal Riset Kesehatan Masyarakat, 2024)
Adolescence is a transitional period from childhood to adulthood. Unintended teenage pregnancy is a global issue that needs attention. Parents play an important role in enhancing adolescents' knowledge by providing them with sex education. However, many parents are busy and may not have enough time to provide such information at home. The failure of the family function in fulfilling its role is the initial trigger for teenagers to engage in deviant behavior, making premarital sexual behavior one of the ways adolescents express frustration towards their parents. The influence of peers is crucial during adolescence as they are concerned about their self-esteem and self-concept. There is an increase in peer influence affecting goal orientation and attitudes. However, peers also influence them through active use of social media such as dating apps and Facebook to find partners.